APLIKASI “HOME CHAT” PADA APLIKASI “INTERNET OF THINGS SMARTHOME” SEBAGAI KOMUNIKASI PERALATAN ELEKTRONIK RUMAH TANGGA DENGAN MANUSIA - laili wahyunita (Universitas Islam Lamongan, 2019)
The development of Internet-of-Thing (IoT) -based technology applied to the housing sector is implemented with the existence of smarthome. Various types of smarthome applications offered by producers, one of them is homechat. This application allows communication of household electronic devices to communicate with humans by using text message media on the smartphone.